TINGKAT KEPUASAN MAHASISWA TERHADAP KUALITAS PELAYANAN PADA UNIVERSITAS STIKUBANK SEMARANG - Kasmari .; RA Marlien (Jurnal Ilmiah Dinamika Teknik, 2018)
The method used in this research is the method of Importance Performance Analysis (IPA). Where in concept is a multi-attribute model. This technique identifies the strengths and weaknesses of service by using two criteria of service quality and student satisfaction. In this study aims to determine the level of student satisfaction with the quality of services provided by the Faculty of Economics and Business University Stikubank Semarang. To know the priority service attributes to be improved and maintained. analyzed with servqual method and cartesian diagram. Servqual method is used to determine the level of service quality based on the gap that occurs between perceptions or performance and student expectations, the dimensions used include: responsiveness, reliability, assurance, emphaty (empathy), and tangibles (tangible). Cartesian diagram is used to identify the priority service attributes to be improved and maintained. Based on the results of the analysis using servqual method states that students of Faculty of Economics and Business University Stikubank Semarang not satisfied with the services provided. The gap value of the tangible dimension is -0.39, reliability -0.60, responsiveness -0.38, empathy -0.24, assurance -0.18. sequentially ie -0.113, -0.046, -0.048, -0.090, -0.059. The result of Cartesius diagram analysis of attributes that become the main priority to be improved (quadrant I) are item 2, 11 20,21, 23 (quadrant II) that is 1, 5, 7, 12, 13, 14, 16, 24, 27 (kudran III ) ie items 3, 8, 10, 18, 19, 20, 26, (quadrant IV) ie items 4, 6, 9, 15, 17, 25. Keywords: Service, Hope, Servqual, Cartesian Diagram, Level of Satisfaction